The Impact of discrimination against minorities on its behavior towards the political system: Case study of Arab-Spring Countries(2007-2017) - Radaideh, Ramzy; Al Shdouh, Emad (Dirasat: Human and Social Sciences, 2021)
This study intends to identify the impact of discrimination against minorities in Arab Spring countries on intensity of their behavior towards the political regime during the period (2007-2017). Starting out from two hypotheses, the study primarily tested a positive steady relationship between discrimination against minorities and intensity of their behavior against the political regime. Secondarily, the study hypothesized that the government-induced discrimination has greater impact on minority’s tendency to violence compared with impact of social discrimination. Relying on the system analysis approach along with comparative and statistical methods, the first hypothesis was confirmed meaning that the minority’s tendency to violence is highly affected by social discrimination, thereby rejecting the second hypothesis. The study concludes that the Arab Spring did not reduce level of government-induced discrimination, rather it exacerbated the degree of social discrimination against minorities,the study recommends the necessity of building a state of citizenship and strengthening the paths of political reform to achieve democracy in order to combat discrimination.